Post-COVID-19 World Philosophy of Functioning: New Globalisation Challenges - Krasivskyy, Orest; Maziy, Natalya; Krasivsky, Denis; Kotygorenko, Viktor; Zhukova, Halyna (Տիգրան Մեծ)
The primary purpose of the study is to characterise the philosophy of functioning of the world. The ar-ticle used general scientific methods, general logical methods of theoretical analysis and specific scientific methods (technical analysis, specification, interpretation, etc.). As a result of the study, the philosophical and social essence of the crisis and pandemic was characterised. It was examined how the crisis and pandemic are affecting the functioning of the suspension and its worldview philosophy and how the crisis and pandemic affect the functioning of the suspension and its philosophy of worldview. The philosophical and social aspect of the pandemic in modern conditions of development and what new globalisation challenges it entails has been investigated.
Keywords: Philosophy